Observations of hard X-rays of auroral origin with Polar Patrol Balloons No. 8 and 10 - Nakamura, Tomokazu; Ebihara, Yusuke; Ejiri, Masaki; Kadokura, Akira; Matsumoto, Naoki; Matsuzaka, Yukihiro; Mukai, Kenji; Murakami, Hiroyuki; Nakagawa, Michio; Namiki, Michiyoshi; Oshima, Naoya; Saito, Yoshitaka; et al. (National Institute of Polar Research, 2004)
P(論文) In the Polar Patrol Balloon (PPB) project, two balloons named PPB-8 and -10 were launched in rapid succession to form a cluster of balloons during their flight on January 13, 2003, from Syowa Station, Antarctica. In order to make the two-dimensional images for auroral X-rays and to obtain the energy spectra of auroras with energy range from 30 keV to 778 keV, the same instruments for hard X-rays were installed on PPB-8 and -10, respectively. These detection systems observed several auroral X-ray events during the flight. In particularly on January 25, 2003, strong auroral events were detected at about 0919 UT by PPB-10 and at 0927 UT by PPB-8. The aurora observed by PPB-10 was observed after about 8 min by PPB-8 located a 650 km west of PPB-10. The energy spectra of the bright aurora at 0919 UT and 0927 UT for PPB-10 and -8 is obtained as E0 = (78+-5) keV and (70+-5) keV, respectively. departmental bulletin paper